National Question in Program Documents of Ukrainian Political Associations of Conservative-Clerical Direction in Western Ukraine (1920-1930) - Demczyszak, Ruslan ` (Studia Warmińskie, 2016)
In the article activity of Ukrainian parties and social and political associations of conservative-clerical direction in Western Ukraine –UKA, UKS, UKNP (UNA)– is explored. The place of national question in their programs is found out. The attitude to the slogan of autonomy of Western Ukraine within Poland and possible independence of Ukraine was researched. It analyzes the decision of party conferences, discussions on this subject on the pages of print media related to political organizations. Looks to character of Ukrainian-Polish relations of metropolitan Andrey Sheptytskyi and bishop Hrygory Khomyshyn are exposed.